Filaments, steel cords, tires
Filaments with copper, zinc, and cobalt plating films, optimized for specific ratios and distributions, provide enhanced adhesion performance in tires, addressing durability needs in high humidity and temperature conditions.
Patent Information
- Application Number
- JP2022514088
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-06
- Filing Date
- 2021-04-06
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2041-04-06
Smart Images

Figure 0007608442000004 
Figure 0007608442000005 
Figure 0007608442000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a filament, a steel cord, and a tire.
[0002] This application claims priority to Japanese Application No. 2020-068581, filed on April 6, 2020, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0003] For example, Patent Document 1 proposes a steel cord for reinforcing rubber, which is made of at least one brass-plated steel wire and is characterized in that the brass-plated steel wire contains 0.001 to 0.1 ppm of cobalt on the extreme surface within a depth of 4 nm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-087687 A Summary of the Invention
[0005] The filament of the present disclosure is a filament having a plating coating, The plating film contains copper, zinc, and cobalt, a cobalt content in the plating film is 0.5% by mass or more and 8% by mass or less, where the total content of copper, zinc, and cobalt in the plating film is taken as 100% by mass; In a longitudinal cross section of the filament including the central axis of the filament, when three observation areas of 1 μm square including the outer surface of the plating film are set along the central axis with a distance of 10 mm between the observation areas, the average area percentage occupied by cobalt in the observation areas is 1% or more and 50% or less. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is an illustration of a filament according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is an enlarged view of area A in FIG. [Figure 3A] FIG. 3A is an explanatory diagram of the observation area. [Figure 3B] FIG. 3B is an explanatory diagram of how to determine the thickness of the region where zinc oxide is distributed. [Figure 3C] FIG. 3C is an explanatory diagram of how to determine the ratio of the copper content in the outer surface region to the copper content in the central region of the plating film. [Figure 4] FIG. 4 is an explanatory diagram of the filament base material. [Diagram 5] FIG. 5 is an explanatory diagram of a plating apparatus that has been conventionally used when forming a Co layer on a filament base material. [Figure 6] FIG. 6 is an explanatory diagram of one configuration example of a plating apparatus that can be suitably used when forming a Co layer of a filament base material. [Figure 7] FIG. 7 is an explanatory diagram of a steel cord according to one embodiment of the present disclosure. [Figure 8] FIG. 8 is a cross-sectional view of a tire according to one embodiment of the present disclosure. [Figure 9] FIG. 9 is an explanatory diagram of the belt layer. [Figure 10] FIG. 10 is an explanatory diagram of a method for measuring durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Problem that this disclosure aims to solve] In recent years, there has been a demand for further improvements in tire performance, and from the viewpoint of improving tire durability, there has been a demand for filaments that have excellent adhesion to tire rubber when used in tires.
[0008] Therefore, an object of the present invention is to provide a filament having excellent adhesive properties with rubber. [Effects of this disclosure]
[0009] According to the present disclosure, a filament having excellent adhesive performance with rubber can be provided.
[0010] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be described. In the following description, the same or corresponding elements are denoted by the same reference numerals, and the same description thereof will not be repeated.
[0011] (1) A filament according to one embodiment of the present disclosure is a filament having a plating coating, The plating film contains copper, zinc, and cobalt, a cobalt content in the plating film is 0.5% by mass or more and 8% by mass or less, where the total content of copper, zinc, and cobalt in the plating film is taken as 100% by mass; In a longitudinal cross section of the filament including the central axis of the filament, when three observation regions of 1 μm square including the outer surface of the plating film are set along the central axis with a distance of 10 mm between the observation regions, the average area proportion occupied by cobalt in the observation regions can be made 1% or more and 50% or less.
[0012] In the following, copper may be referred to as Cu, zinc as Zn, and cobalt as Co.
[0013] When a filament having a plating film is covered with rubber to form a tire, the Cu contained in the plating film reacts with the S (sulfur) contained in the rubber to form an adhesive layer containing CuS on the rubber side of the interface between the filament and the rubber. This adhesive layer has the function of improving the initial adhesive performance of the filament with the rubber. Therefore, the Cu contained in the plating film has the function of improving the initial adhesive performance with the rubber.
[0014] The initial adhesive performance means the adhesive performance between the filament and the rubber immediately after vulcanization during tire production.
[0015] It is believed that the Zn contained in the plated coating controls the reaction that forms the above-mentioned adhesive layer.
[0016] Tires are mounted on vehicles and rotate at high speeds while in contact with the ground, and therefore are exposed to high temperature and humidity for long periods of time. When tires are exposed to high temperature and humidity, moisture and oxygen can permeate the tire rubber and reach the vicinity of the interface between the filament and the rubber, which can cause a decrease in the adhesive performance of the filament with the rubber.
[0017] Therefore, in addition to the initial adhesive performance, the adhesive performance of the filaments is required to be excellent in terms of moisture and heat resistant adhesive performance, which is the adhesive performance between the filaments and the rubber in the tire after it has been placed in a high temperature and high humidity environment.
[0018] When a tire is placed in a high-temperature and high-humidity environment, the moisture that has entered as described above affects the composition of the adhesive layer, and the adhesive performance of the filament to the rubber is thought to decrease. However, in the filament according to one embodiment of the present disclosure, the plating film contains Co, which is thought to suppress changes in the composition of the adhesive layer, and the adhesive performance against heat and moisture is also improved.
[0019] Plating In the membrane Of Cu, Zn, and Co, the Co content (hereinafter also referred to as "Co content in the plating film") is preferably 0.5 mass% or more and 8 mass% or less. By making the Co content in the plating film 0.5 mass% or more, the plating film contains a sufficient amount of Co, and the effect of improving the above-mentioned moisture and heat resistant adhesion performance can be fully exerted. Furthermore, by making the Co content in the plating film 8 mass% or less, the Cu and Zn contents in the plating film can be sufficiently increased, and the initial adhesion ability can also be improved.
[0020] In this way, since the plating coating of the filament according to one embodiment of the present disclosure contains Cu, Zn, and Co, when a tire is manufactured using the filament, the adhesion performance of the filament to the rubber in the tire can be improved. Note that the adhesion performance specifically means the initial adhesion performance and the adhesion performance against heat and moisture.
[0021] However, in recent years, there has been a demand for further improvements in tire performance, and there is a demand for further improvements in the adhesive properties of the filaments with rubber.
[0022] According to the study of the inventors of the present invention, when the plating film of the filament contains Cu, Zn, and Co, Cu and Zn are alloyed in the plating film. In contrast, Co is mainly distributed as a single element in isolated islands near the outer surface of the plating film. It was found that by controlling the distribution of Co, a filament with excellent adhesion to rubber can be obtained.
[0023] As described above, Co is considered to have the function of enhancing the adhesive performance against heat and moisture. However, as described above, Co exists as a single element in the plated film without reacting with Cu or Zn. In the plated film, Co is mainly distributed on the outer surface side of the plated film. Therefore, when the content of Co in the plated film is within the above-mentioned range, by setting the average area ratio of Co in the observation area to 50% or less, the area of the Cu-Zn alloy exposed on the outer surface of the plated film can be sufficiently secured, and the formation of the adhesive layer can be promoted. Therefore, a filament with particularly excellent initial adhesive performance with rubber can be obtained.
[0024] Since Co has the function of enhancing the heat and moisture resistant adhesive performance as described above, when the Co content in the plating film is within the above-mentioned range, the proportion of Co present in the vicinity of the rubber can be sufficiently increased by setting the average area proportion of Co in the observation area to 1% or more, resulting in a filament with particularly excellent heat and moisture resistant adhesive performance with rubber.
[0025] As described above, by setting the average area ratio of Co in the observation area within the above range, a filament having excellent adhesion performance with rubber, i.e., excellent initial adhesion performance and wet heat resistance adhesion performance, can be obtained.
[0026] (2) When 10 observation regions are set along the central axis such that the distance between the observation regions is 10 mm, the average area ratio of cobalt in the observation regions may be 5% or more and 50% or less.
[0027] By increasing the number of observation regions set, even if an observation region having an unusual value for the area proportion of Co in the observation region is included, the influence of the observation region having such an unusual value can be suppressed.
[0028] In addition, when 10 observation regions are set, by setting the average area ratio of Co in the observation regions to 50% or less, it is possible to ensure a sufficient area of Cu-Zn alloy exposed on the outer surface of the plating film for the entire filament, which promotes the formation of an adhesive layer and results in a filament with particularly excellent initial adhesive performance with rubber.
[0029] In addition, when 10 observation regions are set, the ratio of Co present in the vicinity of the rubber can be sufficiently increased by setting the average area ratio of Co in the observation regions to 5% or more, resulting in a filament with particularly excellent heat and moisture resistance adhesive performance with rubber.
[0030] (3) In the cross section, three first observation lines are set along the thickness direction of the plating film such that the distance between the first observation lines is 10 mm, and the thickness of the region in which zinc oxide is distributed is measured along the first observation lines. The average thickness of the region on the first observation straight line in which zinc oxide is distributed may be 0.004 μm or more and 0.007 μm or less.
[0031] Zinc, especially zinc oxide, is thought to control the reaction that forms the adhesive layer. For this reason, by making the average thickness of the region where zinc oxide is distributed 0.004 μm or more, the formation of the adhesive layer is promoted and the initial adhesive performance with the rubber is improved. However, if the average thickness of the region where zinc oxide is distributed is excessively thick, it may actually hinder the formation of the adhesive layer. However, if the average thickness of the region where zinc oxide is distributed is 0.007 μm or less, the initial adhesive performance with the rubber can be sufficiently improved without hindering the formation of the adhesive layer.
[0032] (4) In the cross section, three second observation lines were set along the thickness direction of the plating film such that the distance between the second observation lines was 10 mm, and the copper content was measured along the second observation lines. The thickness of the plating film on the second observation line is T, the copper content in an outer surface region, which is a region on the second observation straight line between the outer surface of the plating film and a point 1 / 3T away from the outer surface of the plating film, is defined as Cu1; If the copper content in the center region on the second observation line, which is the region between the inner surface of the plating film and a point 1 / 3T away from the inner surface of the plating film, is Cu2, The ratio of the copper content in the outer surface region to the copper content in the central region, Cu, calculated by the following formula (A): ratio The average value of may be 90% or more and 97% or less.
[0033] Cu ratio =Cu1÷Cu2×100 (A) The ratio of the copper content in the outer surface region to the copper content in the central region, Cu ratio If the average value is 90% or more, it means that a lot of copper is distributed on the outer surface side. As mentioned above, copper reacts with sulfur to form an adhesive layer containing Cu2S. Therefore, the distribution of a lot of copper on the surface side of the filament promotes the formation of an adhesive layer and particularly improves the initial adhesive performance with the rubber.
[0034] On the other hand, the ratio of the copper content in the outer surface region to the copper content in the central region, Cu ratio By setting the average value to 97% or less, the proportion of cobalt distributed on the outer surface of the plating film, i.e., near the rubber, can be sufficiently increased. As a result, the effect of improving the moisture and heat resistant adhesive performance due to cobalt can be fully exerted, resulting in a filament that is particularly excellent in initial adhesive performance and moisture and heat resistant adhesive performance.
[0035] (5) The degree of processing may be 3.4 or more and 3.8 or less.
[0036] The degree of processing is an index showing the degree to which the filament base material has been drawn, and by making the degree of processing 3.4 or more, the cobalt contained in the plating film of the filament can be sufficiently dispersed within the plating film, resulting in a filament with particularly excellent heat and moisture resistance adhesive properties.
[0037] However, excessive processing may cause the plating film to become thin and the cobalt on the outer surface to peel off. Degree It is preferable that the value is 3.8 or less. Degree By setting the viscosity at 3.8 or less, it is possible to produce a filament with particularly excellent heat and moisture resistance adhesive properties with rubber.
[0038] (6) The steel cord of the present disclosure may include at least one filament according to any one of (1) to (5).
[0039] Since the steel cord according to one embodiment of the present disclosure contains the filaments described above, when used in a tire, the steel cord can have excellent adhesion to tire rubber.
[0040] (7) The tire of the present disclosure may include the steel cord described in (6).
[0041] The tire according to one embodiment of the present disclosure includes the above-described steel cord, and therefore the tire has high adhesion between the steel cord and rubber and excellent durability.
[0042] [Details of the embodiment of the present disclosure] Specific examples of a filament, a steel cord, and a tire according to one embodiment of the present disclosure (hereinafter, referred to as the present embodiment) will be described below with reference to the drawings. Note that the present invention is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0043] [filament] Hereinafter, the filament according to this embodiment will be described with reference to Figs. 1 to 3C. Fig. 1 is a perspective view of a filament 10 according to this embodiment, and Fig. 2 is an enlarged view of region A in Fig. 1. Fig. 3A is a schematic view of an observation region. Fig. 3B is an explanatory diagram of how to determine the thickness of a region where zinc oxide is distributed. Fig. 3C is an explanatory diagram of how to determine the ratio of the copper content in the outer surface region to the copper content in the central region of the plating film.
[0044] The filament according to this embodiment is a filament having a plated coating, and the plated coating can contain copper, zinc, and cobalt.
[0045] When the total content of copper, zinc, and cobalt in the plating film is taken as 100 mass%, the content of cobalt in the plating film can be 0.5 mass% or more and 8 mass% or less. In addition, when a plurality of 1 μm square observation regions including the outer surface of the plating film are set in the plating film in a cross section passing through and parallel to the central axis of the filament, the average area percentage occupied by cobalt in the observation regions can be 1% or more and 50% or less.
[0046] The cross section of the filament in which the observation region is set can also be said to be a cross section in the longitudinal direction of the filament that includes the central axis of the filament.
[0047] The filament 10 of this embodiment may have a wire material 11 and a plating film 12 covering the surface thereof, as shown in Fig. 1. The wire material 11 and the plating film 12 of the filament 10 of this embodiment will be described below. (1) Wire rod The wire 11 may be, for example, a steel wire, and more preferably, a high carbon steel wire. (2) Plating film (About the composition) The plating film 12 may contain Cu (copper), Zn (zinc), and Co (cobalt).
[0048] When the filament 10 having the plating film 12 is covered with rubber to form a tire, the Cu contained in the plating film 12 reacts with the S (sulfur) contained in the rubber to form an adhesive layer containing CuS on the rubber side of the interface between the filament and the rubber. This adhesive layer functions to improve the initial adhesive performance of the filament with the rubber. Therefore, the Cu contained in the plating film 12 functions to improve the initial adhesive performance with the rubber.
[0049] The initial adhesive performance means the adhesive performance between the filament and the rubber immediately after vulcanization during tire production.
[0050] It is believed that the Zn contained in the plating film 12 controls the reaction that forms the above-mentioned adhesive layer.
[0051] Tires are mounted on vehicles and rotate at high speeds while in contact with the ground, and therefore are exposed to high temperature and humidity for long periods of time. When tires are exposed to high temperature and humidity, moisture and oxygen can permeate the tire rubber and reach the vicinity of the interface between the filament and the rubber, which can cause a decrease in the adhesive performance of the filament with the rubber.
[0052] Therefore, in addition to the initial adhesive performance, the adhesive performance of the filaments is required to be excellent in terms of moisture and heat resistant adhesive performance, which is the adhesive performance between the filaments and the rubber in the tire after it has been placed in a high temperature and high humidity environment.
[0053] When a tire is placed in a high-temperature and high-humidity environment, the moisture that has entered as described above affects the composition of the adhesive layer, and the adhesive performance of the filament to the rubber is thought to decrease. However, in the filament 10 of this embodiment, the plating film 12 contains Co, which is thought to suppress changes in the composition of the adhesive layer, and the adhesive performance against moisture and heat can be improved.
[0054] Of Cu, Zn, and Co in the plating film 12, the content of Co is preferably 0.5% by mass or more and 8% by mass or less, more preferably 0.7% by mass or more and 7.95% by mass or less, and even more preferably 2.00% by mass or more and 7.93% by mass or less. The content of Co in the plating film is the content of Co when the total content of Cu, Zn, and Co in the plating film is 100% by mass. By making the content of Co in the plating film 0.5% by mass or more, the plating film contains a sufficient amount of Co, so that the effect of improving the above-mentioned moisture and heat resistant adhesive performance can be fully exerted. In addition, by making the content of Co in the plating film 8% by mass or less, the content of Cu and Zn in the plating film can be sufficiently increased, and the initial adhesive ability can also be improved.
[0055] The Co content in the plating film 12 can be calculated by analyzing the solution in which the plating film of the filament is dissolved, using an atomic absorption analyzer or the like.
[0056] In this manner, in the filament 10 of the present embodiment, since the plating coating 12 contains Cu, Zn, and Co, when the filament is used to manufacture a tire, the adhesive performance of the filament to the rubber in the tire can be improved. Note that the adhesive performance means the initial adhesive performance and the adhesive performance resistant to moist heat. (Average area ratio of Co in the observed area of the plating film) However, in recent years, there has been a demand for further improvements in tire performance, and there is a demand for further improvements in the adhesive properties of the filaments with rubber.
[0057] According to the research of the inventors of the present invention, when the plating film 12 of the filament 10 contains Cu, Zn, and Co, Cu and Zn are alloyed in the plating film 12. In contrast, Co is mainly distributed as a single element in isolated islands near the outer surface of the plating film 12. It was found that by controlling the distribution of Co, a filament with excellent adhesive performance to rubber can be obtained.
[0058] In the filament of this embodiment, when multiple observation regions are set in a cross section passing through and parallel to the central axis of the filament, it is preferable that the average area ratio occupied by Co in the observation regions is within a predetermined range.
[0059] The observation region will be described with reference to FIG. 2. Note that FIG. 2 is a schematic diagram and does not reflect the size of each part. FIG. 2 is an enlarged view of region A in FIG. 1. Region A is a plane that passes through the central axis CA1 of the filament 10 and is parallel to the central axis CA1. In other words, region A is a longitudinal cross section of the filament 10 including the central axis CA1 of the filament 10. In FIG. 1, the X-axis, Y-axis, and Z-axis are shown, but the longitudinal direction of the filament 10 is the direction of the X-axis in FIG. 1, and region A corresponds to the XZ plane including the central axis CA1.
[0060] 2, the observation area 21 can be set in the plating coating 12 portion, and can be set so as to include the plating coating 12 within the observation area 21. The observation area 21 is preferably set so as to include the outer surface 12A of the plating coating 12. The outer surface 12A here refers to the surface of the plating coating 12 opposite to the surface facing the wire 11, and can also be referred to as the surface of the filament 10 and the plating coating 12 exposed to the outside.
[0061] It is possible to set a plurality of observation regions 21. Although Fig. 2 shows an example in which three observation regions 21A, 21B, and 21C are set, the present invention is not limited to this form, and it is preferable to set, for example, 3 to 10 observation regions.
[0062] The observation regions are preferably provided at equal intervals along the central axis CA1 of the filament 10. In the case of FIG. 2, it is preferable that the distance L211 between the observation region 21A and the observation region 21B is equal to the distance L212 between the observation region 21B and the observation region 21C. The distance between the observation regions is not particularly limited, but it is preferable that the distance L211 and the distance L212 are, for example, 10 mm. That is, it is preferable that the observation regions are set such that the distance between the observation regions is, for example, 10 mm along the central axis CA1 of the filament 10.
[0063] FIG. 3A shows a schematic diagram of the observation area 21. FIG. 3A shows one observation area 21. The observation area 21 is an area of 1 μm square, i.e., one Side Therefore, the length L31, L32 of one side of the observation region 21 shown in FIG. 3A is 1 μm.
[0064] 3A, the observation region 21 can include the outer surface 12A of the plating coating 12. As shown in Fig. 3A, it is preferable to configure the observation region 21 so that the outer surface 12A of the plating coating 12 configures one side of the observation region 21. However, since the outer surface 12A of the plating coating 12 usually has fine irregularities, the observation region 21 can be set so as to include a portion of the outer surface 12A of the plating coating 12.
[0065] 3A, the plating film 12 can have a region of Co 121 and a region of alloy 122 in which Cu and Zn are alloyed. However, this does not mean that the Co in the plating film 12 is completely separated from Cu and Zn, and a very small amount of Co may be dissolved in the alloy 122 region.
[0066] Furthermore, according to the investigations of the inventors of the present invention, when three observation regions 21 are set, the average area proportion of Co121 in the observation regions 21 is preferably 1% or more and 50% or less, more preferably 5% or more and 50% or less, even more preferably 9% or more and 50% or less, particularly preferably 20% or more and 50% or less, and most preferably 30% or more and 45% or less.
[0067] As described above, Co is considered to have the function of enhancing the adhesive performance against heat and moisture. However, as described above, Co is considered to exist as a simple substance in the plating film 12 without reacting with Cu or Zn. As shown in FIG. 3A, Co 121 is distributed mainly on the outer surface 12A side of the plating film 12 in the plating film 12. Therefore, when the content of Co in the plating film is within the above-mentioned range, by setting the average area ratio of Co 121 in the observation area 21 to 50% or less, the area of the alloy 122 exposed on the outer surface 12A of the plating film 12 can be sufficiently secured, and the formation of the adhesive layer can be promoted. Therefore, a filament with excellent initial adhesive performance with rubber can be obtained.
[0068] Since Co has the function of enhancing the heat and moisture resistant adhesion performance, when the Co content in the plating film is within the above-mentioned range, the proportion of Co present in the vicinity of the rubber can be sufficiently increased by setting the average area proportion of Co 121 in the observation region 21 to 1% or more. This allows the filament to have excellent heat and moisture resistant adhesion performance with rubber.
[0069] As described above, by setting the proportion of the area occupied by Co in the observation region 21 within the above range, a filament having excellent adhesive strength with rubber, that is, excellent initial adhesive performance and adhesive performance resistant to moist heat can be obtained.
[0070] Furthermore, when 10 observation regions 21 are set and evaluation is performed in the 10 observation regions 21, the average area proportion of Co121 in the 10 observation regions 21 is preferably 5% or more and 50% or less, more preferably 9% or more and 50% or less, even more preferably 20% or more and 50% or less, and particularly preferably 30% or more and 45% or less.
[0071] By increasing the number of observation regions 21 set, even if an observation region having an unusual value for the area ratio of Co in the observation regions is included, the influence of the observation region having such an unusual value can be suppressed.
[0072] When 10 observation regions 21 are set, the average area ratio of Co in the observation regions 21 is set to 50% or less, thereby ensuring a sufficient area of the Cu-Zn alloy 122 exposed on the outer surface 12A of the plating film 12 for the entire filament. This promotes the formation of an adhesive layer, resulting in a filament with particularly excellent initial adhesive performance with rubber.
[0073] In addition, when 10 observation regions 21 are set, the ratio of Co present near the rubber can be sufficiently increased by setting the average area ratio of Co 121 in the observation regions 21 to 5% or more. This allows the filament to have particularly excellent heat and moisture resistant adhesion to rubber.
[0074] When ten observation regions 21 are provided, as in the case of three observation regions, 1 μm square observation regions including the outer surface 12A of the plating film 12 can be set in the plating film 12 in a longitudinal cross section of the filament 10 including the central axis CA1 of the filament 10. In this case, ten observation regions 21 can be set along the central axis CA1 so that the distance between the observation regions is 10 mm.
[0075] The method of determining the area ratio of Co in the observation region 21 is not particularly limited. For example, element mapping in the observation region can be performed using STEM / EDX (Scanning Transmission Electron Microscope / Energy dispersive X-ray spectrometry) or the like. Then, from the obtained element mapping results, the area of Co121 can be calculated, and the area ratio of Co in the observation region 21 can be calculated. The area ratio of Co here means the area ratio of the region where Co exists without reacting with other metals. (Thickness of the zinc oxide distribution area) In a longitudinal cross section of the filament 10 including the central axis CA1 of the filament 10, three first observation lines are set in the plating film 12 in the thickness direction of the plating film 12 such that the distance between the first observation lines is 10 mm. When the thickness of the region where zinc oxide is distributed is measured along the first observation lines, the average thickness of the region where zinc oxide is distributed on the first observation lines is preferably 0.004 μm or more and 0.007 μm or less, and more preferably 0.005 μm or more and 0.006 μm or less.
[0076] The first observation straight line will be described with reference to FIG.
[0077] 2, the first observation straight line 22 can be set in the plating coating 12 portion and can be set along the Z axis in the thickness direction of the plating coating 12, i.e., perpendicular to the central axis CA1, along the Z axis in the figure. The first observation straight line 22 can be drawn between the outer surface 12A of the plating coating 12 and the inner surface 12B of the plating coating 12. The inner surface 12B of the plating coating 12 is the surface of the plating coating 12 that faces the wire 11.
[0078] The first observation straight lines 22 are preferably provided at equal intervals along the central axis CA1 of the filament 10. In the case of FIG. 2, the distance L221 between the first observation straight lines 22A and 22B is preferably equal to the distance L222 between the first observation straight lines 22B and 22C. The distances L221 and L222 are preferably 10 mm. That is, the first observation straight lines 22 are preferably set such that the distance between the first observation straight lines is 10 mm along the central axis CA1 of the filament 10, for example.
[0079] There is no particular limitation on the method for measuring the thickness of the region where zinc oxide is distributed on the first observation line 22. For example, a line analysis of zinc and oxygen can be performed along the first observation line using STEM / EDX or the like.
[0080] FIG. 3B is a schematic diagram showing the line analysis data obtained in this case.
[0081] In Fig. 3B, the horizontal axis indicates the measurement position, and the vertical axis indicates the intensity. As shown in Fig. 3B, when a line analysis is performed from the outer surface 12A to the inner surface 12B of the plating film 12, peaks appear for each element in the regions where zinc (Zn) and oxygen (O) are distributed.
[0082] Therefore, the length of the region where the zinc peak and the oxygen peak overlap can be defined as the thickness T1 of the region on the first observation straight line where zinc oxide is distributed, and the average value of the thicknesses of the regions on the three first observation straight lines where zinc oxide is distributed can be defined as the average thickness of the regions on the filament where zinc oxide is distributed.
[0083] As mentioned above, zinc, especially zinc oxide, is thought to control the reaction that forms the adhesive layer. For this reason, by making the average thickness of the region where zinc oxide is distributed 0.004 μm or more, the formation of the adhesive layer is promoted and the initial adhesive performance with the rubber is improved. However, if the average thickness of the region where zinc oxide is distributed is excessively thick, it may actually hinder the formation of the adhesive layer. However, if the average thickness of the region where zinc oxide is distributed is 0.007 μm or less, the initial adhesive performance with the rubber can be sufficiently improved without hindering the formation of the adhesive layer. (The ratio of the copper content in the outer surface area to the copper content in the central area) Here, in a cross section of the filament 10 in the longitudinal direction including the central axis CA1 of the filament 10, the plating film 12 is Ta Three straight second observation lines are set so that the distance between each second observation line is 10 mm.
[0084] When the copper content is measured along the second observation line, the copper content in the outer surface region located on the outer surface 12A side of the plating film 12 on the second observation line is defined as Cu1. To The copper content in is Cu2.
[0085] At this time, the ratio Cu1 of the copper content in the outer surface region to the copper content in the central region, Cu2, calculated by the following formula (A) is ratio The average value is preferably 90% or more and 97% or less, and more preferably 92% or more and 96% or less.
[0086] Cu ratio =Cu1÷Cu2×100 (A) When the thickness of the plating coating on the second observation line is T, the outer surface region is the region on the second observation line between the outer surface 12A of the plating coating 12 and a point 1 / 3T away from the outer surface 12A of the plating coating 12. The center region is the region on the second observation line between the inner surface 12B of the plating coating 12 and a point 1 / 3T away from the inner surface 12B of the plating coating 12.
[0087] The ratio of the copper content in the outer surface region to the copper content in the central region, Cu ratio If the average value is 90% or more, it means that a lot of copper is distributed on the outer surface side. As mentioned above, copper reacts with sulfur to form an adhesive layer containing Cu2S. Therefore, the distribution of a lot of copper on the surface side of the filament promotes the formation of an adhesive layer and particularly improves the initial adhesive performance with the rubber.
[0088] On the other hand, the ratio of the copper content in the outer surface region to the copper content in the central region, Cu ratio By setting the average value to 97% or less, the proportion of cobalt distributed on the outer surface of the plating film, i.e., near the rubber, can be sufficiently increased. As a result, the effect of improving the moisture and heat resistant adhesive performance due to cobalt can be fully exerted, resulting in a filament that is particularly excellent in initial adhesive performance and moisture and heat resistant adhesive performance.
[0089] The second observation straight line will be described with reference to FIG.
[0090] 2, the second observation line 23 can be set in the plating coating 12 portion and can be set along the Z axis in the thickness direction of the plating coating 12, i.e., perpendicular to the central axis CA1, along the Z axis in the figure. The second observation line 23 can be drawn between the outer surface 12A of the plating coating 12 and the inner surface 12B of the plating coating 12.
[0091] The second observation lines 23 are preferably arranged at equal intervals along the central axis CA1 of the filament 10. In the case of FIG. 2, the distance L231 between the second observation lines 23A and 23B is preferably equal to the distance L232 between the second observation lines 23B and 23C. The distances L231 and L232 are preferably 10 mm. That is, the second observation lines 23 are preferably set such that the distance between the second observation lines is 10 mm along the central axis CA1 of the filament 10, for example.
[0092] We will explain how to calculate Cu1 and Cu2.
[0093] There is no particular limitation on the method for measuring the copper content along the second observation line 23. For example, a line analysis of copper can be performed along the second observation line using STEM / EDX or the like.
[0094] FIG. 3C is a schematic diagram showing the line analysis data obtained in this case.
[0095] In Fig. 3C, the horizontal axis indicates the measurement position, and the vertical axis indicates the intensity. As shown in Fig. 3C, when a line analysis is performed from the outer surface 12A to the inner surface 12B of the plating film 12, a peak appears in the region where copper (Cu) is distributed.
[0096] Here, of the thickness T of the plating film on the second observation straight line, a region with a length of 1 / 3T of the plating film 12 located on the outer surface 12A side is the outer surface region 33. And, for example, the peak area of copper EDX measured in the outer surface region 33 can be defined as Cu1.
[0097] In addition, of the thickness T of the plating film on the second observation straight line, for example, 1 / 3 of the plating film located on the central axis CA1 side, i.e., the inner surface 12B side of the plating film T The region having a length of this is the central region 34. For example, the EDX peak area of copper measured in the central region 34 can be taken as Cu2.
[0098] Using the calculated Cu1 and Cu2, the Cu in each second observation line is calculated according to the above-mentioned formula (A). ratio Then, the Cu in the three second observation lines can be calculated. ratio The average value of the copper content in the outer surface region of the filament to the copper content in the central region of the filament is calculated as Cu ratio It can be taken as the average value of (Regarding the degree of processing) The filament of the embodiment preferably has a processing degree η of 3.4 to 3.8. When the cross-sectional area of the plane perpendicular to the longitudinal direction of the filament base material is S0 and the cross-sectional area of the filament of the embodiment after drawing is S1, η is defined as ln(S0 / S1).
[0099] That is, the degree of processing is an index showing the degree to which the filament base material has been drawn, and by making the degree of processing 3.4 or more, the cobalt contained in the plating film of the filament can be sufficiently dispersed within the plating film, resulting in a filament with particularly excellent heat and moisture resistance adhesion properties.
[0100] However, excessive processing may cause the plating film to become thin and the cobalt located on the outer surface to peel off. Therefore, the processing degree η is preferably 3.8 or less, and by keeping the processing degree η at 3.8 or less, the filament can have particularly excellent heat and moisture resistant adhesive properties with rubber.
[0101] The higher the degree of processing of the filament, the higher the tensile strength. On the other hand, the carbon contained in the filament does not change because it is derived from the material constituting the filament, such as the wire material.
[0102] For this reason, a calibration curve may be prepared in advance for the relationship between the carbon content and tensile strength of the filament and the degree of processing, and the degree of processing may be calculated by measuring the carbon content and tensile strength of the filament. [Filament manufacturing method] A method for producing a filament according to the present embodiment will be described. According to the method for producing a filament according to the present embodiment, the filament described above can be produced. Therefore, some of the matters already described will not be described.
[0103] The method for producing the filament of this embodiment may include the following steps.
[0104] The filament base material production process involves depositing a Cu layer, a Zn layer, and a Co layer on the surface of the wire to form the filament base material.
[0105] A heat treatment process in which the filament base material is heat treated.
[0106] The wire drawing process involves drawing the filament base material after the heat treatment process.
[0107] Furthermore, when the Co layer is formed in the filament base material manufacturing process, the distance between the electrode supplying Co and the wire can be kept constant.
[0108] Each step will be described below. (1) Filament base material production process In the filament base material preparation step, a filament base material can be prepared.
[0109] 4 is a schematic cross-sectional view of the filament base material 40, which is parallel to the central axis CA2 of the filament base material 40 and passes through the central axis. of 4 corresponds to a cross section in the longitudinal direction. In Fig. 4, the X-axis, Y-axis, and Z-axis are shown, and the longitudinal direction of the filament base material 40 is the direction of the X-axis in Fig. 4, and Fig. 4 corresponds to the XZ plane including the central axis CA2. As shown in Fig. 4, the filament base material 40 can have a Cu layer 42, a Co layer 43, and a Zn layer 44 on the surface of the wire material 41. Note that the wire material 41 is a wire material before wire drawing, and can also be called a wire material for base material when distinguished from the wire material of the filament.
[0110] Therefore, in the filament base material fabrication step, a Cu layer 42, a Co layer 43, and a Zn layer 44 can be formed on the surface of the wire 41. The Cu layer, the Co layer, and the Zn layer are preferably formed by plating.
[0111] The order in which the layers are formed is not particularly limited, but for example, it is preferable to form the Co layer 43 and the Zn layer 44 after forming the Cu layer 42 on the wire 41. The order in which the Co layer 43 and the Zn layer 44 are formed is also not particularly limited, but for example, it is preferable to form the Zn layer 44 after forming the Co layer 43.
[0112] A filament can be produced by drawing the filament base material, but a part of the layer disposed on the outermost surface of the filament base material may come into contact with a die or the like during the drawing process and be scraped off. In addition, the preferred thickness of the Co layer 43 is usually thinner than the preferred thicknesses of the Cu layer 42 and the Zn layer 44. Therefore, in order to prevent the Co content in the plating film of the filament obtained after the drawing process from significantly varying from the target composition, it is preferable to form the Co layer 43 before the Zn layer 44 as described above, thereby preventing the Co layer 43 from being scraped off during the drawing process.
[0113] Although the thickness of each layer is not particularly limited, the ratio of each component in the plating coating 12 of the filament 10 obtained after the wiredrawing process changes depending on the thickness of each layer. For this reason, it is preferable to select the thickness of each layer depending on the desired composition of the plating coating 12 on the filament after the wiredrawing process.
[0114] For example, the average value of the thickness T42 of the Cu layer 42 is preferably 0.777 μm or more and 1.290 μm or less, and more preferably 0.800 μm or more and 1.254 μm or less. The average value of the thickness T43 of the Co layer 43 is preferably 0.0121 μm or more and 0.138 μm or less, and more preferably 0.0352 μm or more and 0.0900 μm or less. The average value of the thickness T44 of the Zn layer 44 is preferably 0.246 μm or more and 0.627 μm or less, and more preferably 0.250 μm or more and 0.614 μm or less, and even more preferably 0.306 μm or more and 0.557 μm or less.
[0115] The average thickness of each of the Cu layer, Co layer, and Zn layer can be calculated by measuring at multiple measurement points and averaging them. The number of measurement points is not particularly limited, but is preferably, for example, 3 to 10. It is preferable that the multiple measurement points are set so that the distances between the measurement points in the central axis direction of the filament base material 40 are equal. The distance between the measurement points is not particularly limited, but can be, for example, 10 mm.
[0116] In addition, in the wire drawing process described later, it is preferable to select the size of the wire and the thickness of each layer so that the degree of processing is 3.4 to 3.8. Since the degree of processing has already been described, the description will be omitted here.
[0117] Furthermore, according to the research of the inventors of the present invention, when the Co layer 43 is formed, by forming the Co layer 43 so that its thickness is uniform, it is possible to make the average area ratio of Co in the observation region described above fall within a predetermined range for the filament obtained after the heat treatment process and the wire drawing process.
[0118] As described above, it is preferable that the Co layer 43 has a uniform thickness, and when the thickness is measured at multiple measurement points, the variation ratio is preferably 2.6 or less, and more preferably 2.5 or less. The variation ratio is a value obtained by dividing the difference between the maximum and minimum values when the thickness of the Co layer 43 is measured at multiple measurement points by the average thickness of the Co layer 43, and can be calculated by the following formula (1).
[0119] (Variation ratio) = (Maximum thickness – Minimum thickness) ÷ Average thickness (1) When the thickness of the Co layer 43 is measured at multiple measurement points, the smaller the variation ratio, the more the degree of variation in the thickness relative to the thickness of the Co layer is suppressed, and the more uniform the thickness can be. When the variation ratio of the Co layer 43 is within the above range, the proportion of the area of Co in a predetermined observation region can be easily set to the above range when the filament is drawn into the filament.
[0120] The lower limit of the thickness variation ratio of the Co layer 43 is not particularly limited, but can be set to, for example, 0.6 or more.
[0121] The Co layer can be formed by plating as described above. Conventionally, as shown in FIG. 5, a plating solution 52 and a Co source 53 are placed in a plating tank 51. The Co source 53 can be made of Co metal or granular Co compound.
[0122] An electrode plate 54 is connected to the Co source 53, and the Co source 53 serves as an electrode for supplying Co. Then, in the plating tank 51, the wire 55 is transported from the first roll 551 to the second roll 552, and passed through the plating tank 51, thereby forming a Co layer on the wire 55 of the filament base material.
[0123] 5, however, the distance between the electrode for supplying Co and the wire 55 differs depending on the shape of the Co source 53, which is an electrode for supplying Co. Specifically, the distance between the Co source 53 and the wire 55 differs, for example, such as a distance L531 between the Co source 531 and the wire 55 and a distance L532 between the Co source 532 and the wire 55. For this reason, it has been difficult to form a uniform Co layer on the surface of the wire 55 of the filament base material.
[0124] Therefore, in the filament manufacturing method of this embodiment, it is preferable to keep a constant distance between the electrode that supplies Co and the wire when forming the Co layer. The specific method is not particularly limited, but can be carried out, for example, using a plating apparatus 60 shown in Fig. 6. In the plating apparatus 60 in Fig. 6, the same members as those in the plating apparatus 50 in Fig. 5 are assigned the same numbers and will not be described.
[0125] In the plating apparatus 60 shown in FIG. 6, a wire mesh 61 on which a Co source 53 is arranged is disposed above a wire 55. The Co source 53 is immersed in a plating solution 52. A power source (not shown) is connected to the wire mesh 61, and the Co source 53 serves as an electrode. In this case, since the Co source 53 is disposed on the bottom surface of the wire mesh 61, the distance L6 between the Co source 53 serving as an electrode for supplying Co and the wire 55 can be kept constant regardless of the shape of the Co source 53. Therefore, a Co layer can be formed uniformly on the surface of the wire 55.
[0126] Here, an example is shown in which the Co source 53 is placed above the wire 55 and the wire mesh 61 connected to a power source is arranged, but the present invention is not limited to this form as long as the distance between the wire 55 and the electrode that supplies Co is kept constant. For example, a plate-like body made of a Co source can be used as the electrode that supplies Co, and the distance between the electrode that supplies Co and the wire 55 can be kept constant.
[0127] Although the Cu layer and Zn layer can be formed in the same manner as the Co layer, the Cu layer and Zn layer are thicker than the Co layer, and therefore the difference in thickness uniformity due to the film formation method is smaller than that of the Co layer, and therefore the film formation conditions for these layers are not limited to the above methods. (2) Heat treatment process In the heat treatment step, the filament base material can be heat treated.
[0128] The heat treatment temperature is not particularly limited, but is preferably a temperature equal to or higher than the alloying temperature of Cu and Zn. In particular, the heat treatment temperature is preferably 550°C or higher and 650°C or lower, which is higher than the melting point (419.5°C) at which Zn becomes liquid. The heat treatment time is also not particularly limited, but is preferably, for example, 3 seconds or higher and 7 seconds or lower.
[0129] The heat treatment causes Cu and Zn to form an alloy. (3) Wire drawing process In the wire drawing process, the filament base material after the heat treatment process can be wire drawn.
[0130] The wire drawing process can be carried out to obtain a desired filament diameter.
[0131] The average value of the area ratio occupied by Co in the observation region of the plating film described above, the thickness of the region where zinc oxide is distributed, the ratio of the copper content in the outer surface region to the copper content in the central region, etc. can be adjusted to a desired range by selecting, for example, the manufacturing conditions. Examples of the manufacturing conditions include the conditions of the heat treatment process, the conditions such as the degree of processing in the wire drawing process, and the selection of the conditions for cleaning the surface of the filament base material after the filament base material preparation process or before the wire drawing process.
[0132] [Steel cord] The steel cord according to this embodiment will be described below with reference to FIG.
[0133] The steel cord according to this embodiment can have at least one of the above-mentioned filaments.
[0134] The steel cord of the present embodiment may be composed of one of the above-mentioned filaments. It may also be composed of a plurality of twisted filaments. When the steel cord has a plurality of filaments, at least one of the filaments may be the above-mentioned filament, or all of the filaments may be the above-mentioned filaments.
[0135] When the steel cord of this embodiment has a plurality of filaments, for example, as shown in FIG. 7, a steel cord 70 can be formed by twisting together a plurality of filaments 71.
[0136] 7 shows a steel cord 70 having a 1×4 structure in which four filaments 71 are twisted together in a circumferential direction into one layer, but the present invention is not limited to this configuration. For example, the number of filaments may be three or less, or five or more. The steel cord may also have a structure in which filaments are twisted together into two or more layers.
[0137] The filaments of the steel cord of the present embodiment may be so-called wavy filaments having bent portions and non-bent portions alternately along the longitudinal direction.
[0138] The steel cord of the present embodiment contains the above-mentioned filaments, and therefore, when used in a tire, the steel cord of the present embodiment can be a steel cord with excellent adhesion to tire rubber.
[0139] 〔tire〕 Next, the tire according to this embodiment will be described with reference to FIGS.
[0140] The tire of this embodiment may include the steel cord described above.
[0141] Fig. 8 shows a cross-sectional view of a tire 80 according to this embodiment taken along a plane perpendicular to the circumferential direction. Although Fig. 8 shows only the portion to the left of the center line (CL), the same structure continues to the right of the center line (CL) with the CL as an axis of symmetry.
[0142] As shown in FIG. 8, a tire 80 includes a tread portion 81, a sidewall portion 82, and a bead portion 83.
[0143] The tread portion 81 is a portion that comes into contact with the road surface. The bead portions 83 are provided on the inner diameter side of the tire 80 from the tread portion 81. The bead portions 83 are portions that come into contact with the rim of a vehicle wheel. The sidewall portions 82 connect the tread portion 81 and the bead portions 83. When the tread portion 81 receives an impact from the road surface, the sidewall portions 82 elastically deform to absorb the impact.
[0144] The tire 80 includes an inner liner 84 , a carcass 85 , a belt layer 86 , and a bead wire 87 .
[0145] The inner liner 84 is made of rubber and seals the space between the tire 80 and the wheel.
[0146] The carcass 85 forms the framework of the tire 80. The carcass 85 is composed of organic fibers such as polyester, nylon, rayon, or the like, or steel cords, and rubber. The above-mentioned steel cords can also be used as the carcass 85. That is, the above-mentioned steel cords having at least one filament can also be used as the carcass 85.
[0147] The bead wire 87 is provided in the bead portion 83. The bead wire 87 receives a tensile force acting on the carcass 85.
[0148] The belt layer 86 tightens the carcass 85 to increase the rigidity of the tread portion 81. In the example shown in FIG.
[0149] Fig. 9 is a diagram showing a schematic diagram of two belt layers 86. Fig. 9 shows a cross-sectional view in a plane perpendicular to the longitudinal direction of the belt layer 86, that is, the circumferential direction of the tire 80.
[0150] As shown in Fig. 9, two belt layers 86 are overlapped in the radial direction of the tire 80. Each belt layer 86 has a plurality of steel cords 91 and rubber 92. The plurality of steel cords 91 are arranged in parallel in a row. The rubber 92 covers the steel cords 91, and the entire circumference of each steel cord 91 is covered with the rubber 92. The steel cords 91 are embedded in the rubber 92.
[0151] The steel cord 91 may be a steel cord as described above. That is, the steel cord may have at least one of the filaments as described above. Therefore, the steel cord 91 used in the tire of the present embodiment may be composed of one of the filaments as described above. The steel cord 91 of the present embodiment may also have a configuration in which a plurality of filaments are twisted together. In this case, one or more of the filaments in the steel cord 91 may be the filaments as described above, or all of the filaments may be the filaments as described above.
[0152] The tire of this embodiment includes the above-mentioned steel cord as the steel cord 91. Therefore, the tire of this embodiment has high adhesion performance between the steel cord and rubber, and can be a tire with excellent durability.
[0153] Although the embodiments have been described in detail above, the present invention is not limited to the specific embodiments, and various modifications and changes are possible within the scope of the claims. EXAMPLES
[0154] The present invention will be described below with reference to specific examples, but is not limited to these examples. (Evaluation method) First, the evaluation method of the filament base material and the filament produced in the following experimental examples will be described. (1) Evaluation of filament base material For the filament base material produced in the following experimental example, immediately after forming a plating film on the wire, i.e., immediately after the filament base material production process, the thicknesses of the Cu layer, Co layer, and Zn layer were measured at multiple points on a cross section passing through and parallel to the central axis.
[0155] Three measurement points were provided along the central axis of the filament base material, and the distance between the measurement points in the central axis direction of the filament base material was set to 10 mm.
[0156] The average values of the measured thicknesses of each layer at the measurement points were taken as the average thicknesses of the Cu layer, Co layer, and Zn layer of the filament base material, respectively.
[0157] To measure and calculate the thickness of each layer, first, a STEM / EDX (scanning transmission electron microscope / energy dispersive X-ray analysis) was used to map each element in a cross section passing through and parallel to the central axis of the filament base material. The region of each layer was then determined from the obtained element mapping image, and the thickness of each layer at each of the above measurement points was calculated, and the average value was calculated.
[0158] In Tables 1 to 3, the average thickness of the Cu layer, the average thickness of the Zn layer, and the average thickness of the Co layer are represented as "Cu layer thickness," "Zn layer thickness," and "Co layer thickness."
[0159] In addition, for the Co layer, the difference between the maximum and minimum values measured at the above three measurement points is divided by the average thickness of the Co layer, i.e., the thickness variation ratio for the Co layer calculated using the above-mentioned formula (1) is shown in Tables 1 to 3 as the ``Co layer thickness variation ratio.'' (2) Filament evaluation (2-1) Average area ratio of Co in the observed area of the plating film In a cross section passing through and parallel to the central axis of a filament produced in the following experimental example, three observation regions 21A-21C each measuring 1 μm square were set in the plating film 12. As shown in Figures 2 and 3A, the observation region 21 was set to include the outer surface 12A of the plating film 12. The distances L211, L212 between each of the observation regions 21 were set to 10 mm.
[0160] The area ratio of Co in each observation region was measured and calculated, and the average value of the area ratio of Co in the three (3 places) observation regions was calculated. Places The figures are shown as "average" (average)
[0161] In calculating the average value of the area ratio occupied by Co in each observation region, first, using STEM / EDX (scanning transmission electron microscope / energy dispersive X-ray analysis), mapping of each element in each observation region was performed in a cross section passing through and parallel to the central axis of the filament. Then, the area ratio occupied by Co in the observation region was obtained from the obtained element mapping image, and the average value of the three (3 places) observation regions was calculated.
[0162] In addition, except that the number of observation regions was 10, the area ratio occupied by Co was measured and calculated in each observation region in the same manner, and the average value of the area ratio occupied by Co in the 10 observation regions was calculated. Places The figures are shown as "average" (average)
[0163] Even when the number of observation regions was 10, each observation region was set to include the outer surface 12A of the plating film 12, and the distance between each observation region was 10 mm. In addition, when calculating the average area ratio of Co in each observation region, first, using STEM / EDX, mapping of each element in each observation region was performed in a cross section passing through and parallel to the central axis of the filament. Then, the area ratio of Co in the observation region was obtained from the obtained element mapping image, and the average value of the 10 observation regions was calculated. (2-2) Co content in the plating film A portion of the filament having the plated coating formed and subjected to wire drawing was cut out and immersed in a stripping solution to dissolve the plated coating. The resulting solution was analyzed using an atomic absorption spectrometer (Hitachi High-Technologies Corporation, Model: Z-2300). From the analysis results, the content of Co among Cu, Zn, and Co in the plated coating was calculated. That is, the content of Co in the plated coating was calculated when the total content of Cu, Zn, and Co in the plated coating was taken as 100 mass %. In Tables 1 to 3, this is shown as the "content of Co in the plated coating." (2-3) Machining degree A calibration curve was prepared in advance showing the relationship between the carbon content and tensile strength of the filament and the degree of processing.
[0164] The carbon content and tensile strength of the filaments produced in the following experimental examples were measured, and the degree of processing was calculated using the above calibration curve.
[0165] The carbon content was analyzed using an atomic absorption spectrometer (Hitachi High-Technologies Corporation, Model: Z-2300).
[0166] The tensile strength was measured using an autograph (manufactured by Shimadzu Corporation, model: AGS-5kNX). (2-4) Thickness of the zinc oxide distribution area In a longitudinal cross section of the filament 10 including the central axis CA1 of the filament 10, three straight first observation lines 22 were set on the plating film 12 along the thickness direction of the plating film 12, with the distances L221, L222 between the first observation lines 22 being 10 mm.
[0167] Then, a line analysis was performed for zinc and oxygen along the first observation line using STEM / EDX. In this case, the length of the region where the zinc peak and the oxygen peak overlap was defined as the thickness T1 of the region where zinc oxide was distributed, as shown in FIG. 3B.
[0168] For each first observation straight line, the thickness of the region where zinc oxide is distributed was measured as described above, and the average value of the thicknesses of the regions where zinc oxide is distributed measured for the three first observation straight lines was calculated. The results are shown in the "ZnO thickness" column in the table. (2-5) The ratio of the copper content in the outer surface region to the copper content in the central region In a longitudinal cross section of the filament 10 including the central axis CA1 of the filament 10, three straight second observation lines 23 were set on the plating film 12 along the thickness direction of the plating film 12, with the distances L231, L232 between the second observation lines being 10 mm.
[0169] Then, a line analysis was performed for copper along the second observation line using STEM / EDX.
[0170] As shown in FIG. 3C, when a line analysis of copper is performed along the second observation straight line from the outer surface 12A to the inner surface 12B of the plating film 12, a peak appears in the region where copper (Cu) is distributed.
[0171] In this case, the thickness of the plating film on the second observation straight line was defined as T, and the region on the second observation straight line between the outer surface 12A of the plating film 12 and a point 1 / 3T away from the outer surface 12A of the plating film was defined as the outer surface region 33. The copper EDX peak area measured in the outer surface region 33 was defined as the surface side copper content Cu1.
[0172] The region on the second observation line between the inner surface 12B of the plating film 12 and a point 1 / 3T away from the inner surface 12B of the plating film 12 was defined as the center region 34. of The peak area was taken as the central copper content, Cu2.
[0173] From the results of the measurements on each second observation straight line, the ratio of the copper content in the outer surface region to the copper content in the central region, Cu, was calculated using the following formula (A). ratio The Cu calculated from the measurements on the three second observation lines was ratioThe average value of the copper content in the outer surface region of the filament was calculated as the average ratio of the copper content in the central region of the filament. The results are shown in the column "Cu ratio (surface side / center side)" in the table.
[0174] Cu ratio =Cu1÷Cu2×100 (A) (2-6) Adhesion performance index (Initial adhesion performance) The filaments produced in each of the following experimental examples were embedded in unvulcanized rubber to form filament-rubber composites, which were then vulcanized at 160° C. for 20 minutes to produce evaluation samples.
[0175] In accordance with ASTM-D-2229-93a, the steel cord was pulled out from the prepared evaluation sample, and the pull-out force was measured to evaluate the initial adhesive performance. The evaluation was expressed as an index, with the value of Experimental Example 16 being 100. The larger the value, the better the result.
[0176] In Tables 1 to 3, the results are shown as "initial" in the adhesive performance index. (Wet and heat resistant adhesive performance) The evaluation samples were prepared under the same conditions as those for the initial adhesive performance.
[0177] The evaluation samples were then subjected to a moist heat resistance test in which they were held in a constant temperature and humidity oven set at a temperature of 80°C and a relative humidity of 95% in the air for 300 hours. The evaluation samples after the moist heat resistance test were subjected to the same pull-out force measurement as in the case of the initial adhesive performance, and the moist heat resistance adhesive performance was evaluated. The evaluation was expressed as an index, with the value of Experimental Example 16 being 100. The higher the value, the better the result.
[0178] In Tables 1 to 3, the results are shown as "moisture and heat resistance" as an index of adhesive performance. (2-7) Durability index The filaments produced in each of the following experimental examples were embedded in unvulcanized rubber to form a filament-rubber composite. The filament-rubber composite was then vulcanized at 160° C. for 20 minutes. A string-shaped test specimen including the filament and having a cross-sectional shape of 5 mm thick and 10 mm wide was taken out of the vulcanized filament-rubber composite with a cutter knife.
[0179] Then, as shown in FIG. 10, the obtained specimen 100 was placed on a first roller 1011, a second roller 1012, and a third roller 1013, each having a roller diameter of 25 mm. When placing the specimen 100 on the above three rollers, the positions of the rollers were adjusted so that the specimen 100 located between the first roller 1011 and the second roller 1012 and the specimen 100 located between the second roller 1012 and the third roller 1013 were parallel to each other, as shown in FIG. 10. In addition, a load of 29.4 N was applied along the longitudinal direction to the specimen 100 placed on the first roller 1011 to the third roller 1013. Then, as a movement in the first direction, the first roller 1011 to the third roller 1013 were rotated, and the specimen 100 was moved in the direction of the arrow 101 in FIG. 10. Next, as a movement in the second direction, the first roller 1011 to the third roller 1013 were rotated in the reverse direction, and the test specimen 100 was moved in the direction opposite to the arrow 101 in the figure. The above-mentioned operation of the movement in the first direction and the movement in the second direction was considered as one set, and this operation was repeated. The rotation speed of each roller was set so that the above-mentioned reciprocating movement could be performed 100 times per minute. Then, the number of sets of the above-mentioned reciprocating movement of the test specimen was counted until the test specimen broke.
[0180] The evaluation is shown as a relative value with the result of Experimental Example 16 set at 100. (Conditions for each experiment) Filaments were produced under the following conditions and evaluated.
[0181] Experimental Examples 1 to 15 are examples, and Experimental Examples 16 to 21 are comparative examples. [Experimental Example 1] The filaments were produced according to the following procedure. (1) Filament base material production process A Cu layer 42, a Co layer 43, and a Zn layer 44 were sequentially plated and laminated on the surface of a steel wire 41 to produce a filament base material 40 (see FIG. 4).
[0182] The Cu layer was formed using copper pyrophosphate as the plating solution, the Co layer was formed using cobalt sulfate as the plating solution, and the Zn layer was formed using zinc sulfate as the plating solution.
[0183] When each layer was formed, the current density, the linear speed of the wire fed into the plating bath, and the composition and concentration of the plating solution were adjusted so that each layer had a desired thickness.
[0184] The Co layer was formed by using a plating apparatus 60 shown in Fig. 6 while maintaining a constant distance L6 between a Co source 53 serving as an electrode for supplying Co and a wire 55. The configuration of the plating apparatus 60 has already been described, and therefore will not be described here.
[0185] C in the obtained filament base material u Table 1 shows the evaluation results of the average thicknesses of the Zn layer, the Co layer, and the difference between the maximum and minimum thicknesses of the Co layer divided by the average thickness of the Co layer, i.e., the thickness variation ratio for the Co layer described above. (2) Heat treatment process The filament base material was heat-treated by heating it at 600°C for 5 seconds in an air atmosphere to diffuse the metal components and form a plating film. (3) Wire drawing process The obtained wire having the plated coating was subjected to a wire drawing process to obtain a filament having a plated coating and a filament diameter of 0.55 mm.
[0186] The obtained filament base material and filament were evaluated as described above. The evaluation results are shown in Table 1. [Experimental Examples 2 to 15] In the filament base material preparation process, the filament was prepared in the same manner as in Experimental Example 1, except that the current density, the linear speed of the wire fed to the plating tank, and the composition and concentration of the plating solution were adjusted so that each layer had the desired thickness when it was formed.
[0187] The obtained filament base material and filament were evaluated as described above. The evaluation results are shown in Tables 1 and 2. [Experimental Examples 16 and 17] In the filament base material preparation process, the Co layer was not formed, and only the Cu layer and the Zn layer were formed. Then, when forming each layer, the current density, the linear speed of the wire fed to the plating tank, and the composition and concentration of the plating solution were adjusted so that each layer had the desired thickness. Except for the above points, the filament was prepared in the same manner as in Experimental Example 1.
[0188] The obtained filaments were evaluated as described above. The evaluation results are shown in Table 3. [Experimental Examples 18 to 21] In the filament base material preparation process, the current density, the linear speed of the wire supplied to the plating tank, and the composition and concentration of the plating solution were adjusted so that each layer had a desired thickness. In addition, the plating device 50 shown in FIG. 5 was used to form the Co layer. Therefore, when the Co layer was formed, the distance between the Co source 53, which is an electrode that supplies Co, and the wire 55 varied depending on the location. Apart from the above, the filament was prepared in the same manner as in Experimental Example 1.
[0189] The obtained filament base material and filament were evaluated as described above. The evaluation results are shown in Table 3.
[0190] [Table 1]
[0191] [Table 2]
[0192] [Table 3] From the results in Tables 1 to 3, it was confirmed that in Experimental Examples 1 to 15, filaments were obtained that had a plating coating containing Cu, Zn, and Co, and when three observation areas were set, the average area percentage of Co in the observation area was 1% or more and 50% or less.
[0193] In addition, it was confirmed that the filaments of Experimental Examples 1 to 15 were superior in initial adhesive performance and wet heat resistant adhesive performance, in other words, superior in adhesive performance to rubber, compared to the filaments of Experimental Examples 16 to 21 which did not satisfy the above requirements.
[0194] It was also confirmed that the filaments of Experimental Examples 1 to 15 were excellent in durability index. Therefore, in a tire using a steel cord including the filaments of Experimental Examples 1 to 15, the durability is also improved and the lifespan can be extended, so that the replacement frequency can be reduced. [Explanation of symbols]
[0195] 10 Filaments 11 Wire rod 12 Plating film Area A CA1 center axis 12A outer surface 12B Inner surface XX axis (longitudinal direction) YY axis ZZ axis (thickness direction) 21, 21A, 21B, 21C Observation area 22, 22A, 22B, 22C First observation line 23, 23A, 23B, 23C Second observation line L211, L212 distance L221, L222 distance L231, L232 distance 121 Co 122 alloy L31, L32 Length of one side 33 Outer surface area 34 Center side area T1 ZnO thickness T plating thickness 40 Filament base material 41 Wire rod 42 Cu layer 43 Co layer 44 Zn layer T42 Thickness T43 Thickness T44 Thickness CA2 center axis XX axis (longitudinal direction) YY axis ZZ axis 50 Plating Equipment 51 Plating tank 52 Plating Solution 53, 531, 532 Co source 54 Electrode plate 55 Wire rod 551 Roll 1 552 Roll 2 L531, L532 distance 60 Plating Equipment 61 Wire Mesh L6 distance 70 Steel Cord 71 Filament 80 Tires 81 Tread 82 Sidewall 83 Bead section 84 Inner Liner 85 Carcass 86 Belt Layer 87 Bead wire CL Center Line 91 Steel Cord 92 Rubber 100 test specimens 1011 First Roller 1012 Second Roller 1013 Third Roller 101 Arrow
Claims
1. A filament having a plating coating, The plating film contains copper, zinc, and cobalt, a content of cobalt in the plating film is 0.5% by mass or more and 8% by mass or less, relative to a total content of copper, zinc, and cobalt in the plating film being 100% by mass; A filament in which, in a longitudinal cross section of the filament including the central axis of the filament, when three observation regions of 1 μm square including the outer surface of the plating film are set along the central axis with a distance of 10 mm between the observation regions, the average area ratio occupied by cobalt in the observation regions is 34.4% or more and 50% or less.
2. The filament according to claim 1, wherein when 10 observation regions are set along the central axis with a distance between the observation regions of 10 mm, the average area ratio occupied by cobalt in the observation regions is 5% or more and 50% or less.
3. In the cross section, three first observation lines were set in the plating film along the thickness direction of the plating film such that the distance between the first observation lines was 10 mm, and the thickness of the region in which zinc oxide was distributed was measured along the first observation lines.
3. The filament according to claim 1, wherein the average thickness of the region on the first observation straight line in which zinc oxide is distributed is 0.004 μm or more and 0.007 μm or less.
4. In the cross section, three second observation lines were set in the plating film along the thickness direction of the plating film such that the distance between the second observation lines was 10 mm, and when the copper content was measured along the second observation lines, The thickness of the plating film on the second observation straight line is T, the copper content in an outer surface region, which is a region on the second observation straight line between the outer surface of the plating film and a point 1 / 3 T away from the outer surface of the plating film, is defined as Cu1; If the copper content in a center side region on the second observation straight line, which is a region between the inner surface of the plating film and a point 1 / 3 T away from the inner surface of the plating film, is denoted by Cu2, The ratio of the copper content in the outer surface region to the copper content in the central region, Cu, calculated by the following formula (A): ratio The filament according to any one of claims 1 to 3, wherein the average value of is 90% or more and 97% or less. Cổ ratio =」1÷」2×100 ・・・(A)
5. The filament according to any one of claims 1 to 4, having a degree of processing of 3.4 to 3.
8.
6. A steel cord comprising at least one filament according to any one of claims 1 to 5.
7. A tire comprising the steel cord according to claim 6.
Citation Information
Patent Citations
Rubber reinforcement steel cord and manufacturing method for the same
JP2016087687A
Steel cord and method for producing the same
JP2017075384A
Plated steel wire, steel cord and rubber-steel cord complex
JP2018119189A
Plated steel wire, steel cord and rubber-steel cord complex
JP2018119190A
Plated steel wire, steel cord and rubber-steel cord complex
JP2018119191A